Doctor Zhivago - Pasternak, Boris Leonidovich, 1890-1960.; Sharif, Omar, 1932-2015.; Christie, Julie; Metro-Goldwyn-Mayer.; MGM/UA Home Video (Firm) (New York : MGM/UA Home Video, 1980)
An adaptation of the novel of the same title by Boris Pasternak, about a Russian doctor whose life and fate become inextricably bound to the turmoil of civil unrest created by events of World War I and a revolution in his homeland.
VHS format.
MGM/UA Home Video: MV90003.
Vidorecording of the 1965 motion picture released by Metro-Goldwyn-Mayer.
Screenplay by Robert Bolt ; music by Maurice Jarre.
Omar Sharif, Julie Christie, Geraldine Chaplin, Rod Steiger.
Keywords: Feature films